Effect of trans-resveratrol on oxidative stress biomarkers associated with atherosclerosis - Santana, Tamires Miranda (2022)
Growing evidence indicates that oxidative stress plays an important role in the pathophysiology of many cardiovascular diseases, including atherosclerosis. In this context, the use of bioactive compounds with antioxidant action can bring health benefits, especially in the prevention and control of pathophysiological events. Studies suggest that the polyphenol trans-resveratrol can reduce oxidative stress by acting on the nuclear factor erythroid-2-related factor 2 (Nrf2) and this effect would be associated with dosage. Thus, the present study aimed to investigate the effect of different doses of trans-resveratrol on biomarkers related to atherosclerosis and oxidative stress. In the first step, 27 randomized clinical trials, which evaluated the effect of trans-resveratrol on atherosclerosis-related biomarkers, were classified according to their protocol characteristics and profile of each outcome. Biochemical data from 12 biomarkers were selected to calculate the net change (%). Using multivariate analysis, the trials were distributed into 3 clusters. The studies that composed Clusters II and III were more effective in improving blood pressure and reducing dyslipidemia, respectively. These studies were characterized by a longer intervention time (> 2 months) with doses of around 200-500 mg/day. These results showed that the effects of transresveratrol are mainly related to dosage and intervention time. Based on these results, two doses were selected to apply in an experimental protocol to investigate the effect of trans-resveratrol on hepatic oxidative stress biomarkers mediated by Nrf2 pathway. LDLr(-/-) mice were fed for 8 weeks on a standard diet, followed by over 24 weeks on a Western diet, both containing trans-resveratrol at doses of 250 mg/kg diet/day (low dose resveratrol, LRD) or 400 mg/kg diet/day (high dose resveratrol, HRD). A control group (CONT) was maintained without supplementation. In general, both doses of trans-resveratrol did not affect the body weight and lipid profile of the animals. Only the LRD group showed reduced levels of two important biomarkers of oxidative stress in the liver (GSH/GSSG ratio and malonaldehyde), besides to reduced expression of factor nuclear kappa B (NF-kB). However, contrary to our hypothesis, both doses reduced Nrf2 expression in the liver compared to the CONT group. Regarding inflammatory cytokines, no changes were observed in the levels of TNF-α and IL-10. Furthermore, both doses increased the level of the pro-inflammatory cytokine IL-6. Taken together, our results suggest that trans-resveratrol supplementation at doses lower than 500 mg/day may contribute to the reduction of biomarkers related to atherosclerosis and oxidative stress.